Children's perception toward their private music lessons / Elfera Gloria Birly - Birly, Elfera Gloria (2017)
In 1983, formal music education became a compulsory subject in all elementary schools in Malaysia (Nor, 2011). However, "personal instruction at the piano and other European musical instruments has been available outside the public schools since the beginning of this century" (Abdullah, 1990, p. 47). During the colonial times, the British brought trained musicians from India and Philippines to Malaysia to assist the forming and needed for military marching bands. Abdullah (1990) emphasized that these imported musicians were believed to be the ones who initiated the tradition of providing private instructions of European classical music in Malaysia. Private music lesson is a class involving music teaching of instruments such as piano, violin, guitar and voice. Private music lessons can be conducted in groups or individually. According to Abdullah (1990), piano private lesson is the most popular music lesson in Malaysia.